Changes in the choice of anaesthetic techniques for caesarean sections among Turkish citizens and migrants during the COVID-19 pandemic: an interrupted time series analysis - Sevim Baltali; Mehmet Baltali; Ayşegül Ercan; Umut Deniz Akdağ; Mehmet Toptaş (BMC Pregnancy and Childbirth)
Abstract Background The aim of the study was to examine the impact of the COVID-19 pandemic on changes in the choice of anaesthetic techniques for singleton caesarean sections among Turkish citizens and migrants before, during the first year of the COVID-19 pandemic, and after vaccination. Methods This single-center, retrospective observational study was conducted at a tertiary care hospital in Istanbul, Turkey. It included data from 9,744 consecutive women—7,083 (72.7%) Turkish citizens and 2,661 (27.3%) migrants—who underwent singleton caesarean sections between March 2018 and March 2023. The primary outcome was the change in monthly utilization rates of neuraxial anaesthesia (NA) during the COVID-19 pandemic. Secondary objectives included caesarean section urgency and neonatal outcomes. Results During the study period, there was an increasing trend in the number of caesarean sections performed using NA among Turkish citizens and migrants (relative ratio [RR] 1.003, P < 0.001 and RR 1.005, P < 0.01, respectively). Both groups showed a significant immediate increase in the usage rate of NA at the onset of the COVID-19 pandemic (RR 1.095, P < 0.001 and 1.134, P < 0.001, respectively). The introduction of vaccination had no effect on the use of NA (RR 0.970, P = 1.004, and RR 1.000, P = 0.99, respectively). The significant between-group difference in the pre-pandemic usage rate of NA diminished following the onset of the COVID-19 pandemic, with no significant between-group difference observed after vaccination (93.3% vs. 90.9%., P = 0.006, 98.4% vs. 97.1%, P = 0.0; 95.4% vs. 95.2%, P = 0.801, respectively). Category-1 caesarean section events increased throughout the study period (471(10.7%) before COVID-19, 321(17.0%) during the first year, and 700 (20.2%) after vaccination; P < 0.001). There were no significant differences in the incidence of composite adverse neonatal outcomes (stillbirths, Apgar 5-min score < 7) among the three time periods (89(2.0%), 41(2.2%), and 49(1.4%); P = 0.065). Conclusion During the COVID-19 pandemic, our study revealed a continuation of the upward trend in the use of NA for caesarean sections.